2020
DOI: 10.1038/s41586-020-2196-x
|View full text |Cite|
|
Sign up to set email alerts
|

Virological assessment of hospitalized patients with COVID-2019

Abstract: Coronavirus disease 2019 (COVID -19) is an acute infection of the respiratory tract that emerged in late 2019 1,2 . Initial outbreaks in China involved 13.8% of cases with severe courses, and 6.1% of cases with critical courses 3 . This severe presentation may result from the virus using a virus receptor that is expressed predominantly in the lung 2,4 ; the same receptor tropism is thought to have determined the pathogenicity-but also aided in the control-of severe acute respiratory syndrome (SARS) in 2003 5 .… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

363
6,942
31
227

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 6,592 publications
(7,754 citation statements)
references
References 28 publications
363
6,942
31
227
Order By: Relevance
“…Both provide insights of the transmissibility of COVID19, but from two different aspects. Our findings are largely consistent with the currently available data of viral shedding studies in the close contacts and the confirmed cases[10][11]. However, a difference should be noticed that the infection time distribution is more likely to be affected by the sociological factors and non-pharmaceutical interventions performed by local public health authorities.Our findings should be interpreted with caution.…”
supporting
confidence: 91%
“…Both provide insights of the transmissibility of COVID19, but from two different aspects. Our findings are largely consistent with the currently available data of viral shedding studies in the close contacts and the confirmed cases[10][11]. However, a difference should be noticed that the infection time distribution is more likely to be affected by the sociological factors and non-pharmaceutical interventions performed by local public health authorities.Our findings should be interpreted with caution.…”
supporting
confidence: 91%
“…The SARS-CoV-2 load to municipal wastewater was estimated using excretion rates in human stool recently reported by Zhang et al, (2020e) and Wölfel et al (2020), and assuming a fecal load in the range of 100 -400 g feces/day/person, and a fecal density of 1.06 g/mL (Brown and Butler, 1996).…”
Section: Estimation Of Initial Sars-cov-2 Loads In Wastewatermentioning
confidence: 99%
“…This mass load translates into concentrations of 0.15 to 141.5 million viral genomes per liter of wastewater generated in North America and Europe. This is based on the presence of between a reported 600,000 (Zhang et al, 2020e) to 30,000,000 (Wölfel et al, 2020) viral genomes of SARS-CoV-2 per mL of fecal material, and assuming a fecal load of 100 -400 g feces/day/person with a density of 1.06 g/mL (Brown and Butler, 1996). A further refinement of the lower and upper bounds estimate is desirable and will be informed by future studies providing more comprehensive information on virus shedding by symptomatic and asymptomatic infected individuals.…”
Section: Virus Occurrence and Detectability In Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Although these particular studies relate to longitudinal studies of infected patients, the data is not disaggregated per patient. Some authors have however presented sequential test data from individual patients [5,6,10] . Here we use the latter type of data to characterise how the probability of a false-negative test result depends on the number of days between the onset of symptoms and the performance of the test and how this is affected by the site from which swabs are taken.…”
Section: Introductionmentioning
confidence: 99%